Rajasthan Water Assessment : Potential for Private Sector Interventions - Hooda, Sweta Mirdha (International Finance Corporation, New Delhi, 2017)
Water is an essential natural resource; a key building block of life. However, water use has grown at over twice the population growth rate in the last century. As a result, an increasing number of regions are now chronically short of water. Over 1.4 billion people currently live in river basins where use of water exceeds minimum recharge levels. If current water practices continue unchecked, future projections indicate that, by 2025, two-thirds of the world population could be living under severe water stress conditions. Managing and ensuring sustainable use of scarce water resources is one of the main development challenges facing countries, states, and corporations around the world. IFC is committed to working in the water sector, as water has become an increasing business risk for our clients. In India, Rajasthan is one of the most water deprived states with respect to rainfall and per capita water availability. The state faces acute water scarcity challenges as rainfall patterns are impacted by climate change. Increasing agricultural and industrial demand is placing additional pressure on the state’s dwindling water resources. Rajasthan has some of the lowest supplies of drinking water in India with only 162 of 222 towns in the state receiving regular supply of drinking water with the poor being the most affected. Rajasthan needs more holistic and integrated management of its water resources. Collective action is necessary to bring together the public sector, the private sector, civil society, and other stakeholders to work together towards integrated and participatory solutions for water resources planning and management. This report provides an in-depth and comprehensive overview of the challenges of drinking water supply, water quality, and agriculture-water in Rajasthan with a focus on potential private sector engagements. The report offers solutions such as improved technologies and practices for optimal farm productivity, awareness building and infrastructure development through community engagement.